ANALISIS BIBLIOMETRIK MENGGUNAKAN VOSVIEWER: TREND RISET KETERAMPILAN BERPIKIR SISTEM DALAM PENDIDIKAN KIMIA - Amida, Nadia (University of Bengkulu, 2024)
This study examines the development of systems thinking skills research in chemistry education. The method used is bibliometric analysis with the help of the VOSViewer application. The research was conducted in 4 stages, namely: 1) collecting publication data using the Scopus database using the keyword